(untitled) (Economic and Political Thought, 2014)
The main task of the work is an evaluation of the dollar and euro relationship as the world currencies and their historical comparison. The author argues that the causative factor of the appreciation trap for the British pound at the Bretton Woods conference was not the USA’s, as a state or national institution, choice but the Russian spying penetration of the Roosevelt administration. At that time, Kremlin was interested in weakening the British state as a colonial power. Doing it, with the help of H. Dexter White, a Russian spy, representing the Roosevelt administration, was a good opportunity to make progress in that field. As for the appreciation trap for the Japanese yen at the Plaza conference, the author points out to a different but similarly effective causative factor, namely the Hayek- Friedman neoliberal doctrine that had been implemented into practice by the Fed’s chief Allan Greenspan. The doctrine narrowed the central bank emissions of the dollar to the GDP growth. It was a kind of pathology that opened new opportunities for the commercial banking sector to pump into financial markets the credit money and toxic assets playing a role of virtual quasi-commodity instruments. That was simply an improper international intervention. According to the author, both historical examples are no longer characteristic of the USA political and economic system. Quite the opposite, the free trade zone between the US and EU, being an integration grouping, can be expected to introduce partnership and coordination of the dollar and euro rates of exchange. It does not mean, however, an expansion of the euro. Objective conditions will rather favour the dollar.